2000
DOI: 10.1063/1.1289498
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from boron-doped polycrystalline diamond film at the nanometer level within grains

Abstract: Defect structure and electron field-emission properties of boron-doped diamond films Field emission from chemical vapor deposited diamond and diamond-like carbon films: Investigations of surface damage and conduction mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In previous work, 6 we have reported nanometer scale inhomogeneities observed within single grains of as-grown H terminated CVD diamond layers. Those results showed that the inhomogeneities were at the 5-10 nm scale.…”
Section: Yamadamentioning
confidence: 97%
“…In previous work, 6 we have reported nanometer scale inhomogeneities observed within single grains of as-grown H terminated CVD diamond layers. Those results showed that the inhomogeneities were at the 5-10 nm scale.…”
Section: Yamadamentioning
confidence: 97%
“…4,5 In other experiments, the standard scanning tunneling microscope ͑STM͒ work function measurement technique 6 has been modified to obtain micron-scale maps of the geometric enhancement factors of niobium surfaces. It is, therefore, impossible to measure the emission characteristics of individual nanostructures and hence to determine the true effect of the geometric enhancement factor of the structure.…”
mentioning
confidence: 99%